Analisis Kemampuan Pemecahan Masalah Matematis dengan Menerapkan Teori Pirie-Kieren dalam Pembelajaran Merdeka Belajar - Zaqya, Nurul Intan (J-PiMat : Jurnal Pendidikan Matematika, 2024)
Â The objective of this study is to gain insight into students' mathematical problem-solving abilities by applying the Pirie-Kieren theory in Merdeka Belajar learning. This type of research is descriptive qualitative, with an initial sample size of 30 seventh-grade students at SMPN 1 Pandeglang, selected using purposive sampling. Data were collected through tests and semi-structured interviews. The results of the problem-solving ability test data analysis indicate that 27% of students are in the high category, 40% are in the medium category, and 33% are in the low category. Students in the high category can complete 4 stages of problem solving, namely understanding the problem; planning the solution; implementing the solution; and checking back to ensure that all layers of understanding have been fulfilled, that is Primitive Knowing; Image Making; Image Having; Property Noticing; Formalising; Observing; Structuring; Inventising. Students in the medium category can complete 3 stages: understanding the problem, planning the solution, implementing the solution. They also fulfill 6 layers of understanding: Primitive Knowing, Image Making, Image Having, Property Noticing, Formalising, Observing. Students in the low category only complete 2 stages: understanding the problem and implementing the solution. They also fulfill 3 layers of understanding: Primitive Knowing, Image Making, Property Noticing